An Experiment of Game Promotion and Selling Using Twitter - Indika, Deru R; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2013)
— The combination of the internet, social media and mobile phones makes the social mobile game is becoming a huge market with high growth rates from year to year. This trend is attract the game developers/publisher vying to enter this game market including in Indonesia. In other hand, Twitter as one of social media has a major influence on consumer purchase decisions especially in social mobile games. Consumer seeking recommendation about game that they want to download based on their friend recommendation and content that their consume in social media before visit online store. As for Indonesia game developers most of their marketing activities were more to game gathering or events, there is little that effectively use social media as marketing channel. Social media adoption including twitter in Indonesia game developer is at stage of connectivity and proff of company existance. The purpose of this research is to know does using twitter as social media marketing have effect to influence consumer and download mobile game. In this research, experiment methodology was employed. Experiment was choosed because to have real insight about the effect of twitter as social media marketing in building games relationship with consumer and increase the number of game download. Stack The Stuff, game from PT. Nightspade was choosed as research object. The implementation using OASIS frawework as guidance. The results from the experiments in this research measured using Social Model Exposure-Engagement-Influence-Action from Don Bartholomew.Twitter as media marketing executed by carrying experiment 1 (15 August 2012 - 15 September 2012) with buzzing methods first, after it finish, followed by experiment 2 (22 September - 22 October 2012) with tweeting and offering method. Then, both experiment results compared to know which the better Twitter marketing method. The measurement using several tools, namely TweetLevel, Sprout Social, and downloads data. With confidence level 95%, our results suggested that twitter as media marketing with buzzing method have effect to increase game download and tweeting and offering method have effect to increase product engagement and influence in Twitter. Furthermore, in the end of research, there are recommendations to implement twitter as social media marketing for small-middle sized company like Indonesia game developers Keywords: Twitter, social media marketing, experiment methodology, Social Model Exposure-Engagement-Influence-Action